Service-Learning Konseling untuk Penguatan Resiliensi Kesehatan (Health) dan Kesejahteraan (Well-Being) Para Santri di Masa Pandemi - Arifin, Samsul (Proceedings of Annual Conference on Community Engagement, 2022)
One of the important issues during the pandemic is the decline in the health and well-being of the students. The focus of service is health and well-being resilience through counseling services. The purpose of this community service is to describe the application of counseling services to the "Pesantren Tangguh" program at the Salafiyah Syafi'iyah Islamic Boarding School in Situbondo. Community service using a service-learning approach involving Islamic Guidance and Counseling (BPI) students at the Da'wah Faculty and Psychology students at the Faculty of Social Sciences and Humanities, Ibrahimy University and ustadz. The results of this service show that counseling services for health resilience and well-being of the students are balanced between lahiriyah and batiniyah, namely by using the techniques (1) uzlah (self-quarantine), (2) uswah hasanah (social model), (3) megha 'kalemmar aéngnga sé ta' lekkoa (live peer model), (4) mauidhah hasanah (psychoeducation), (5) gerbat (prayer), (6) art, and (7) targhib-ta'zir (reinforcement-punishment), Community service This is the development of the "Islamic Guidance and Counseling" course and some counseling that integrates religion with culture.